Cooperation of LIM domain‐binding 2 (LDB2) with EGR in the pathogenesis of schizophrenia - Tetsuo Ohnishi; Yuji Kiyama; Fumiko Arima‐Yoshida; Mitsutaka Kadota; Tomoe Ichikawa; Kazuyuki Yamada; Akiko Watanabe; Hisako Ohba; Kaori Tanaka; Akihiro Nakaya; Yasue Horiuchi; Yoshimi Iwayama; et al. (EMBO Molecular Medicine)
Abstract Genomic defects with large effect size can help elucidate unknown pathologic architecture of mental disorders. We previously reported on a patient with schizophrenia and a balanced translocation between chromosomes 4 and 13 and found that the breakpoint within chromosome 4 is located near the LDB2 gene. We show here that Ldb2 knockout (KO) mice displayed multiple deficits relevant to mental disorders. In particular, Ldb2 KO mice exhibited deficits in the fear‐conditioning paradigm. Analysis of the amygdala suggested that dysregulation of synaptic activities controlled by the immediate early gene Arc is involved in the phenotypes. We show that LDB2 forms protein complexes with known transcription factors. Consistently, ChIP‐seq analyses indicated that LDB2 binds to > 10,000 genomic sites in human neurospheres. We found that many of those sites, including the promoter region of ARC, are occupied by EGR transcription factors. Our previous study showed an association of the EGR family genes with schizophrenia. Collectively, the findings suggest that dysregulation in the gene expression controlled by the LDB2‐EGR axis underlies a pathogenesis of subset of mental disorders.